1999
DOI: 10.1271/bbb.63.2059
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of the 16-kDa Allergen, RA17, in Rice Seeds. Prediction of the Secondary Structure and Identification of Intramolecular Disulfide Bridges

Abstract: The 16-kDa rice allergen, RA17, belonging to the alpha-amylase/trypsin inhibitor family was isolated from rice seed and structurally characterized by identifying cystine-containing peptides and predicting the secondary structure and hydrophobic regions. Eight peptides, which constitute three sets of cystine-containing peptides, were purified by HPLC from a thermolytic digest of RA17 and identified by their amino acid sequence and composition, indicating five intramolecular disulfide bridges: Cys34-Cys94, Cys26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…To date, proteins suspected as being an allergen to rice are 14 to 16 kDa Ory s 12 (profillin A) and 33 kDa or 35 kDa Ory s 1 (beta-expansin)5-7,9). The majority of plant food allergens can be grouped into only 4 protein families.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, proteins suspected as being an allergen to rice are 14 to 16 kDa Ory s 12 (profillin A) and 33 kDa or 35 kDa Ory s 1 (beta-expansin)5-7,9). The majority of plant food allergens can be grouped into only 4 protein families.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported that globulin in the embryonic bud of rice has strong allergenicity. Another study reported that albumin with protein bands of 14-16 kDa is the major allergen of rice5,6). There are some reports about the protein bands of 26, 33, 56 kDa as the major IgE-binding components in rice7-10).…”
Section: Introductionmentioning
confidence: 98%
“…Some examples of sequence comparison and analysis in the study of allergens include molecular characterization of an allergen group from dust mites (36), characterization of a superfamily of proteins containing the allergenic lipid transfer proteins (37), structural characterization of a rice allergen (38), cross-reactivity studies of allergens (27,39), analysis of mutations of pollen allergens (23), study of structural and molecular basis of allergenicity (25), and identification of characteristic motifs in cat (40) or cockroach (24) allergens.…”
Section: Common Bioinformatic Toolsmentioning
confidence: 99%
“…All these observations suggest that intramolecular disulfide bonding contributes positively to allergenicity. However, there has been little comprehensive analysis of cereal proteins from the standpoint of disulfide bonding (Izumi et al 1999).…”
Section: Identification Of Disulfide Proteins In the Salt Soluble Framentioning
confidence: 99%